Problematics of Murabaha Agreement in Indonesian Islamic Banking: A Systematic Literature Review - M Nur Ikhwan; Inna Khoridatul Bahiya; Awaludin Taufiq; Aditya Darmawan; Fahri Safagutan (Velocity: Journal of Sharia Finance and Banking, 2025)
This study aims to investigate the dynamics and challenges of Murabaha practices in Indonesian Islamic banking. Using a systematic literature review (SLR) method, it examines 17 peer-reviewed articles published between 2014 and 2024, retrieved from Google Scholar and Scopus databases. The study finds that Murabaha is the most dominant financing contract in Indonesian Islamic banking and plays a crucial role in supporting national economic development, particularly through micro, small, and medium enterprise (MSME) financing. However, findings reveal widespread use of the annuity method and frequent violations of ownership principles in Murabaha bil wakalah contracts, posing significant Sharia compliance risks. These challenges are further exacerbated by non-transparent margin setting, limited knowledge among practitioners and customers, weak regulatory oversight, and the preference of Islamic banks for operational simplicity and liquidity over strict adherence to Sharia principles. Such practices may undermine the authenticity and credibility of Islamic financial instruments. To address these concerns, this study recommends improving Sharia literacy among implementers and customers, and strengthening the institutional role and authority of the Sharia Supervisory Board (DPS). These steps are essential to ensure that Murabaha financing remains compliant with Islamic legal principles and contributes effectively to the ethical development of Indonesia’s Islamic banking sector.